High-efficiency dual-axis solar tracking development using Arduino: article / Mohd Ashraf Mohd Zulkifli, Maizatul Zolkapli and Syed Abdul Mutalib Al-Junid Syed Abdul Rahman - Mohd Zulkifli, Mohd Ashraf; Zolkapli, Maizatul; Syed Abdul Rahman, Syed Abdul Mutalib Al-Junid (2012)
The renewable-energy sector is fast gaining ground as a new growth area for numerous countries with the vast potential it presents environmentally and economically. Solar energy plays an important role as a primary source of energy, especially for rural area. This paper presents the design and development of high efficiency dual-axis solar tracking system using Arduino platform. Furthermore, the ultimate objective of this project is to trace the maximum sunlight source to power the solar panel. The project is divided into two stages, which are hardware and software development. In hardware development, five light dependent resistor (LDR) has been used for capturing maximum light source. Two servo motors have been used to move the solar panel at maximum light source location sensing by LDR. Moreover, the code is constructed using C programming language and targeted to Arduino UNO controller. The efficiency of the system has been tested and compared with static solar panel on several time intervals, and it shows the system react the best at the 10-minutes intervals with consistent voltage generated. Therefore, the system has been proven working for capturing the maximum sunlight source for high efficiency solar harvesting applications.